Influence of annealing temperature and measurement ambient on TFTs based on gas phase synthesized ZnO nanoparticles - Walther, Sabine; Schäfer, Stefan; Jank, M. P. M.; Thiem, H.; Peukert, Wolfgang; Frey, Lothar; Ryssel, Heiner (Microelectronic Engineering, 2010)
In this paper, we report on the applicability of gas phase synthesized ZnO nanoparticles for printed electronics. Electrical characteristics of thin film transistors with an active layer based on ZnO nanoparticle dispersions are presented. A low charge carrier mobility and a low Ion/Ioff ratio are found for the devices when measured in nitrogen atmosphere. The mobility is limited by the rough interface between semiconductor and dielectric. Additional electrical measurements in dry air reveal a dependency of the Ion/Ioff ratio on surface states of the ZnO particles. It is shown that adsorption of oxygen on ZnO nanoparticles leads to improved transistor characteristics.
Keywords: Nanoparticle; Printable electronics; Thin film transistor; Zinc oxide